Eksperimentasi teknik-teknik resist pada fabrik denim terbuang bagi rekaan fesyen pakaian - Mohamad Shukri, Bin Che Ya. (unimas, 2014)
Textile resist is an art of pattern design making which creates through a process called resist dyeing. There are variety of textiles resist such as batik and shibori (tie-dye). Textile resist undergoes certain processes of pattern design for example by pinching method, tying or stitching the fabric through one medium which can block the dye. This research focuses on the experimentation of resist techniques on used denim fabric as apparels fashion design. The chosen resist techniques have a potential in giving the added value to used denim fabric from aesthetic aspect and innovation in apparels fashion design. The outcome of this research hopefully can give an opportunity to all designers and consumer who favors textile resist design with the denim fabric custom to produce a creative and innovative design.